The South Carolina Surgical Quality Collaborative: A New Effort to Improve Surgical Outcomes in South Carolina. Issue 6 (June 2018) - Lockett, Marka; Turley, Chris; Gibbons, Lorri; Stinson, Shawn; Adams, James L.; Cole, David; Baliga, Prabhakar K.
Regional surgical quality Collaboratives are improving surgical quality and cutting costs by building regional relationships that leverage information sharing to improve outcomes. The South Carolina Surgical Quality Collaborative (SCSQC) is a new regional surgical quality Collaborative focused on improving general surgery outcomes in South Carolina. It is a joint effort which brings together the skills and resources of Health Sciences South Carolina, the South Carolina Hospital Association, and the Blue Cross Blue Shield of SC Foundation to create a web-based data collection system to provide real-time outcomes data to participating surgeons, and establishing a supportive network for sharing best practices and promoting data driven quality improvement. Members of the SCSQC abstracted more than 8000 general surgery cases from eight participating hospitals in its first year. These facilities are spread across the state of South Carolina and range from large academic referral centers to small community hospitals. The resulting data should be representative of much of the surgical care provided in South Carolina. Monthly conference calls and quarterly face-to-face meetings occur with site Surgeon Leads, site Surgical Clinical Quality Reviewer, and Collaborative leaders. Each site is pursuing a quality improvement project addressing issues identified from analysis of their initial data. Early results on these efforts are encouraging. The SCSQC is a new regional surgical quality Collaborative, which leverages multiple state resources, builds on the successes of similar Collaboratives in Michigan and Tennessee, with the goal to improve the quality and value of general surgical care for South Carolinians.